A novel distributed architecture for unmanned aircraft systems based on Robot Operating System 2 - Lorenzo Bianchi; Daniele Carnevale; Fabio DelFrate; Roberto Masocco; Simone Mattogno; Fabrizio Romanelli; Alessandro Tenaglia (IET Cyber-systems and Robotics, 2023)
Abstract A novel distributed control architecture for unmanned aircraft system (UASs) based on the new Robot Operating System (ROS) 2 middleware is proposed, endowed with industrial‐grade tools that establish a novel standard for high‐reliability distributed systems. The architecture has been developed for an autonomous quadcopter to design an inclusive solution ranging from low‐level sensor management and soft real‐time operating system setup and tuning to perception, exploration, and navigation modules orchestrated by a finite‐state machine. The architecture proposed in this study builds on ROS 2 with its scalability and soft real‐time communication functionalities, while including security and safety features, optimised implementations of localisation algorithms, and integrating an innovative and flexible path planner for UASs. Finally, experimental results have been collected during tests carried out both in the laboratory and in a realistic environment, showing the effectiveness of the proposed architecture in terms of reliability, scalability, and flexibility.